Neurosurgical Equipment Donations: A Qualitative Study - Sichimba, Dawin; Bandyopadhyay, Soham; Ciuculete, Ana Catinca; Erhabor, Joshua; Kotecha, Jay; Egiz, Abdullah; Bankole, Nourou Dine Adeniran; Higginbotham, George; Dalle, David Ulrich; Kanmounye, Ulrick Sidney (Frontiers in Surgery, 2022)
Introduction Neurosurgical equipment donation from high-income countries (HICs) to low-and-middle income countries (LMICs) exists. However, there is currently no published literature on whether there is a need for neurosurgical equipment donations or how to design equipment donation programmes that meet the needs of LMIC neurosurgeons. The primary aims of this study were to explore: (1) the need for the donation of neurosurgical equipment from the UK and Ireland to LMICs within the African continent, and (2) the ways through which neurosurgical equipment donations could meet the needs of LMIC neurosurgeons. Methods This was a qualitative study using semi-structured, one-on-one, audio-recorded interviews. Purposive sampling was used to recruit and interview consultants or attending neurosurgeons from Ireland, the UK and LMICs in Africa in a continuous process until data saturation. Interviews were conducted by members of the Association of Future African Neurosurgeons during March 2021. Qualitative analysis used a thematic approach using open and axial coding. Results Five HIC and 3 LMIC neurosurgeons were interviewed. Five overarching themes were identified: (1) inequality of access to neurosurgical equipment, (2) identifying specific neurosurgical equipment needs, (3) importance of organisations, (4) partnerships between LMIC and HIC centres, and (5) donations are insufficient in isolation. Conclusion There is a need for greater access to neurosurgical equipment in LMICs. It is unclear if neurosurgical equipment donations are the optimal solution to this issue. Other solutions that are not linked to dependency need to be explored and executed. Collaborative relationships between LMICs and HICs better ensures that neurosurgical equipment donations meet the needs of the recipients. These relationships may be best created within an organisation framework that has the logistical capabilities of coordinating international equipment donation and providing a quality control measure.